DETEKSI DINI BATU GINJAL - Shinta, Anita Lidesna (Universitas Nusa Cendana, 2022)
Kidney is one of the important organs of the body that plays a role in maintaining the stability of the extracellular environment that supports the function of all body cells. Kidney stones are one of the most common causes of kidney damage in Kupang, East Nusa Tenggara. Early detection is an early preventive step that can protect the kidneys from permanent damage.